Exploring multi-domains of Islamic finance education curriculum - Syed Jaafar Alhabshi, Syed Musa (IIUM PRESS, International Islamic University Malaysia, 2017)
With exponential growth in the Islamic financial services industry (IFSI), issues on the quality of Islamic finance curriculum and professional development, relevant to the sustainability of the IFSI have been raised in both academia and industry. In particular, the definitions of Islamic finance and program nomenclature of Islamic finance programmes need clarification and systemization to facilitate the development of meaningful and coherent Islamic finance education initiatives. The fundamentals of Islamic education and its relevance to Islamic finance, are highlighted in this concept paper to emphasize the importance of the nature of man as an ethical being, infused with right and proper knowledge in Islamic finance education. Derived principles involving finance behaviour with reference to ‘efficiency’ or ‘opportunistic gains’ are re-examined in the light of Shari’ah based on the sources of belief, values and practice of the Religion of Islam. This is to facilitate clarity in the definition of Islamic finance and the purpose of Islamic finance education. Furthermore, the Malaysian Qualifications Agency (MQA) Muamalat Islamic Finance (MIF) Standard was analysed to explore the domains for an inclusive Islamic finance curriculum domain framework to facilitate the development of ‘fit and proper’ Islamic finance educators and professionals. Shari’ah prescribed guiding principles and rulings are then discussed within the legal and economic perspectives of banking, capital markets and takaful/insurance. This paper reaffirms the essence of Islamic finance education, given proper adab and akhlaq, in realizing the goals of the maqasid al-Shari’ah in Islamic finance